2021
DOI: 10.36778/jesya.v4i2.390
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Zakat, Infak Sedekah, dan Inflasi Terhadap Kemiskinan di Indonesia

Abstract: Kemiskinan merupakan salah satu permasalahan besar yang dialami di setiap negara. Berbagai bentuk kebijakan dan peraturan telah dilakukan dengan tujuan meminimalisir besarnya tingkat kemiskinan. Dari mulai bentuk makro dan mikro telah dilakukan. Namun dengan tingkat populasi dan permasalahan yang terus meningkat belum juga mampu mengatasi permasalahan kemiskinan. Dalam Islam terdapat beberapa berbagai instrumen yang mampu menjawab dan mengatasi permasalahan kemiskinan, yaitu berupa zakat, infak dan sedekah. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
2
5
0
Order By: Relevance
“…In this study it was explained that there was a signi cant effect of receiving zakat on reducing the number of poor people. While infaq/alms do not have a signi cant/negative relationship (Murobbi, 2021).…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 95%
“…In this study it was explained that there was a signi cant effect of receiving zakat on reducing the number of poor people. While infaq/alms do not have a signi cant/negative relationship (Murobbi, 2021).…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 95%
“…Hasil penelitian menunjukan bahwa penanggulangan kemiskinan yang dilakukan oleh pihak BAZNAS pada kota Makassar melalui beberapa program didalamnya, program perkembangan aqidah akhlak bagi mustahik dan program lainnya yang membantu masyarakat Makassar agar lebih baik lagi dari berbagai aspek. Selanjutnya penelitian Murobbi & Usman (2021). hasil penelitian menunjukan bahwa zakat memiliki hasil yang signifikan, namun pada infaq hasil tidak memiliki hubungan yang signifikan terhadap variabel kemiskinan di Indonesia.…”
Section: Pendahuluanunclassified
“…Poverty is a fundamental problem felt by developing countries, including Indonesia [2]. Poverty is a vital problem faced every year, the Central Statistics Agency (BPS) revealed that missions are considered as the inability to meet basic needs [3]. Word Bank interprets the mission as signifying the deprivation of well-being, in short, their income is less than $5 per day or if converted using the current rupiah exchange rate, it is approximately Rp.…”
Section: Introductionmentioning
confidence: 99%
“…Word Bank interprets the mission as signifying the deprivation of well-being, in short, their income is less than $5 per day or if converted using the current rupiah exchange rate, it is approximately Rp. 71,000.00 [3] According to data reported by the Central Statistics Agency (BPS) as of September 2020, the number of poor Indonesians is approximately 27 million, of which women are dominated the poor [4]. The number of poor people in Indonesia is still relatively high [5].…”
Section: Introductionmentioning
confidence: 99%